RESISTENCIA FLEXURAL DE CEMENTOS RESINOSOS: EVALUACIÓN IN VITRO - Noa-Yarasca, Socorro (2025)
Objective: To evaluate the flexural strength of three dental resin cements. Materials and methods: Sixty bars measuring 25x2x2 mm were made of RelyX-U200, RelyxTM Universal and Duo-Link Universal cements. These bars were divided into 3 groups according to brand (n=20) and were kept in distilled water for 24 hours at 37ºC. The 3-point bending test was carried out, according to ISO 4049, in a universal testing machine at a speed of 0.5 mm/min until fracture. Statistical analysis was performed with the Python statistical package, using the one-way Anova test and Tukey's multiple comparisons test with a confidence level of 95%. Results: Duo-Link Universal cement obtained the highest average with respect to flexural strength (104.7±7.8 MPa). Statistically significant differences were found between the three groups (p< 0.001). These differences were present between RelyxTM Universal - Duo-Link Universal (p<.001) and Duo-Link Universal – RelyX U200 (p< .001) cements, while no statistically significant differences were found between RelyxTM Universal and RelyX U200 cements. Conclusion: Duo-Link Universal cement presents greater flexural strength compared to RelyX-U200 and RelyxTM Universal cements. The results indicate that Duo-Link Universal is ideal for restorations requiring high flexural strength, offering greater clinical durability, especially in areas of greater functional load and extensive restorations such as indirect prostheses or posts.